Reimagining art therapy for the digitally-mediated world: a Hexagonal Relationship. Issue 3 (3rd July 2022) - Haywood, Sarah; Grant, Bridget
ABSTRACT: Art Therapists have long been aware of the intersubjective complexities that are evoked in art therapy in relation to images, art-making and their attendant processes. These have often been understood with reference to the psychodynamic concepts of transference and countertransference. In this paper we ask, what happens to these processes when art therapy moves online and becomes digitally-mediated? How do the dynamics of 'the Virtual' affect the image and art-making, and the therapeutic relationship? Drawing on Schaverien and Jung's ideas about transference and countertransference, we propose a new model or 'map' of Art Therapy which helps to think about these questions, which we call a 'Hexagonal Relationship'. To date, published literature has tended to foreground the logistics and practicalities of moving art therapy online, with consideration of complex interpersonal dynamics occupying less of a central space in emerging narratives about digitally-mediated art therapy. We suggest that applying our model to practice could potentially support art therapists to access deeper, less conscious and perhaps more symbolic levels of material in online work, in service of the client's process. We invite art therapists and clients to consider our model with reference to their own experiences of digitally-mediated art therapy, and to test out our questions and hypotheses in their own contexts. Plain-language summary: Art Therapists work with the idea that the images made in art therapy are affected by the relationship between the person making the image (often known as 'the client'), the art therapist, and the environment in which the art therapy session takes place. Making and reflecting on images is a way of understanding and working with whatever is going on for the client, both in their 'external' life and also in their 'internal world' (for example, their thoughts, feelings, imaginings and beliefs). A lot of art therapy now happens online, particularly since the start of the COVID-19 pandemic, and we are all part of the digital world in terms of how we communicate and relate with others. We think it is helpful to consider how art therapy (including the therapeutic relationship, art-making processes and the images made) might be affected by the digital environment and so we have written this paper to explore these ideas. We show readers a diagram of what we call the 'Hexagonal Relationship' to help explain what we mean. We think this will help us to understand more of what happens in art therapy in the digital world, making this kind of therapeutic help more effective and meaningful for clients and their art therapists. We hope that clients and art therapists will test out these ideas for themselves and come into a conversation with us (perhaps through papers like this one, published in art therapy journals) about how well our ideas stand up to actual experience.